Down-regulation of Gfi-1 expression by TGF-β is important for differentiation of Th17 and CD103(+) inducible regulatory T cells - Zhu, Jinfang (The Rockefeller University Press, 2009)
Growth factor independent 1 (Gfi-1), a transcriptional repressor, is transiently induced during T cell activation. Interleukin (IL) 4 further induces Gfi-1, resulting in optimal Th2 cell expansion. We report a second important function of Gfi-1 in CD4 T cells: prevention of alternative differentiation by Th2 cells, and inhibition of differentiation of naive CD4 T cells to either Th17 or inducible regulatory T (iTreg) cells. In Gfi1(−/−) Th2 cells, the Rorc, Il23r, and Cd103 loci showed histone 3 lysine 4 trimethylation modifications that were lacking in wild-type Th2 cells, implying that Gfi-1 is critical for epigenetic regulation of Th17 and iTreg cell–related genes in Th2 cells. Enforced Gfi-1 expression inhibited IL-17 production and iTreg cell differentiation. Furthermore, a key inducer of both Th17 and iTreg cell differentiation, transforming growth factor β, repressed Gfi-1 expression, implying a reciprocal negative regulation of CD4 T cell fate determination. Chromatin immunoprecipitation showed direct binding of the Gfi-1–lysine-specific demethylase 1 repressive complex to the intergenic region of Il17a/Il17f loci and to intron 1 of Cd103. T cell–specific Gfi1 conditional knockout mice displayed a striking delay in the onset of experimental allergic encephalitis correlated with a dramatic increase of Foxp3(+)CD103(+) CD4 T cells. Thus, Gfi-1 plays a critical role both in enhancing Th2 cell expansion and in repressing induction of Th17 and CD103(+) iTreg cells.